NILAI-NILAI PENDIDIKAN KARAKTER DALAM AL-QUR’AN SURAT AL-AN’AM AYAT 151-153 DAN IMPLEMENTASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - SUHARTO SUHARTO (QATHRUNÂ, 2020)
Character education has become an interesting issue to discuss among education practitioners lately. This is because the world of education has so far been seen as constrained by absolute interests. Only concerned with intellectual intelligence, reason and reasoning without being accompanied by an intensive development of intellect in the heart, feelings and emotions or what is often known as character education. This research was conducted at SMK Negeri 1 Cilegon. This type of research is a qualitative field research. Data collection techniques using observation, interviews, documentation. The methodical approach uses study analysis by examining all the data obtained by the author from various sources using semantic analysis and observation. This study uses theory According to D. Yahya Khan, "character education" teaches habits "ways of thinking and" behaviors that "help" individuals to "live and work together as" family, "society, and" nation. As well as' helping others to make 'responsible decisions'. In other words, "character education" teaches students "to think intelligently, activating the" middle brain "naturally. also analyzed the Al-quran Surat Al-An'am Verses 151-153. Then the theory and analysis results are implemented in the learning process of Islamic Religious Education and religious extracurricular activities. The results of this study indicate that (1) In the al-qur'an surah Al-An'am verses 151-153, it contains character values ​​such as religious values, honesty, responsibility, social care and courtesy and curiosity. - Partial character values ​​have also been implemented in religious extracurricular and learning activities including Islamic studies, Islamic Holidays (PHBI) activities.